Instilling Religious Moderation Values in the EFL Classrooms in Islamic Universities: Teachers’ Perspective - Fauzan, Umar; Nadia, Nadia (Indonesian Journal of EFL and Linguistics, 2025)
This qualitative phenomenological study employed the Critical Discourse Analysis methodology developed by Fairclough. English lecturers at three Indonesian universities-Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, Universitas Islam Negeri Antasari Banjarmasin, and Universitas Islam Negeri Sunan Ampel-are the main sources of data for this study. Data-documentation sources, such as literature reviews from research sources, including proceedings, journal articles, theses, and dissertations, provided secondary data for this study on discourse development. Fairclough created critical discourse analysis, which was utilized to analyze the research data. According to this discourse analysis, the English-speaking classes fully incorporate the aspects of moderate Islamic viewpoints that the Indonesian government advocates, such as national unity, tolerance, non-violence, and cultural groundedness. These characteristics of moderate religion are intentionally emphasized by lecturers through their ideological content and participative forms. In other words, by incorporating essential components into their texts and structures, the classes linguistically replicate state-mandated religious moderation. This indicates that English language instruction and the development of values that are required more generally in Indonesian higher education are in systematic agreement.